2018
DOI: 10.1177/0706743717751693
|View full text |Cite
|
Sign up to set email alerts
|

Patient, Treatment, and Health Care Utilization Variables Associated with Adherence to Metabolic Monitoring Practices in Children and Adolescents Taking Second-Generation Antipsychotics

Abstract: Findings from this study highlight the need for better metabolic monitoring for children and adolescents taking SGAs. Enhanced focus on opportunities for multidisciplinary collaboration is needed to improve the quality of care offered to this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 52 publications
7
20
0
1
Order By: Relevance
“…Our study findings were in line with previous studies that suggested that SGA treatment poses major metabolic risks for children (6,7,26). Despite these findings, and the existing guidelines, monitoring practices have often remained irregular (16)(17)(18)(19)(20). In our study, the baseline information necessary for detecting changes in growth and the laboratory test values were seldom complete.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our study findings were in line with previous studies that suggested that SGA treatment poses major metabolic risks for children (6,7,26). Despite these findings, and the existing guidelines, monitoring practices have often remained irregular (16)(17)(18)(19)(20). In our study, the baseline information necessary for detecting changes in growth and the laboratory test values were seldom complete.…”
Section: Discussionsupporting
confidence: 88%
“…These findings highlight the need for proper monitoring practices for children treated with SGAs. There are guidelines on follow-up practices, but there has been limited systematic monitoring, despite the evidence of SGA-related adverse reactions (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…As adolescents are particularly susceptible to atypical antipsychotic-induced weight gain, increased metabolic monitoring is urgently recommended for improving treatment outcomes [ 38 40 ]. Weight gain may decrease medication adherence [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies also sought to distinguish which atypical antipsychotic was prescribed. They made it possible to assess the relative frequency of prescription of one drug compared to others within the same class, although rarely an estimate of prevalence (Raebel et al 2014;Chen et al 2018;Coughlin et al 2018). In a large U.S. study on the monitoring of diabetic risk in 16,000 children and adolescents from 10 North American sites receiving an atypical antipsychotic, 31% were receiving aripiprazole (the first prescription being risperidone, 43%), leading to the conclusion that monitoring was very poor since only 11% of the children and adolescents had their glucose or hemoglobin A1C monitored (Raebel et al 2014).…”
Section: Us Epidemiological Data On Aripiprazolementioning
confidence: 99%